Control of Parametrically-Dependent Linear Systems: A Single Quadratic Lyapunov Approach - Becker, Gregory; Packard, Andy; Philbrick, Doug; Balas, Gary (American Control Conference, 1993, 1993)
In this paper two parameter-dependent control problems for linear, parametrically varying (LPV) systems are presented. Sufficient conditions for exponential stability and an induced L 2 -norm performance objective are given. The resulting synthesis problems are reformulated into convex optimization problems which can be solved with efficient new algorithms.